(untitled) (Global Journal of Human-Social Science, 2024)
After an analysis of the state of the art in today s educational landscape an innovative and transformative learning system Transe Learning is proposed Its general outlines its connections to the wisdom traditions of mankind will be taken into consideration and its applicability in contemporary society will be highlighted in the context of education as an integral and transformative process that accompanies the individual throughout the evolutionary arc of his or her life span development Finally Transe- cognition will be presented as the system of thought necessary to draw on the resources offered by Transe Learning outlining its cornerstones such as Second Attention Further Mode and Integral Thinking